STUDI KASUS DAMPAK PELATIHAN MEDIA PEMBELAJARAN IPS TERHADAP KOMPETENSI PEDAGOGIS GURU DI SEKOLAH DASAR NEGERI 04 SUSUKAN - Qodariah, Lelly; Armiyati, Laely (MAJALAH ILMIAH WIDYA, 2012)
A Learning quality is based on teacherâs quality. The teacher as a director of teaching should have a good pedagogical competencewhich the Indicators are able to implementation learning strategy and using media education. The purpose of this paper is to findout how the training can increase pedagogical competence of teacherâs elementary school in social studies. The method of thispaper is case study in SD Negeri Susukan 04 Pagi. The result showed that training can increase pedagogic competence of teacherof elementary school.